A pilot-scale study of a powdered activated carbon-membrane bioreactor for the treatment of water with a high concentration of ammonia. Issue 1 (10th September 2015) - Shao, Senlin; Qu, Fangshu; Liang, Heng; Chang, Haiqing; Yu, Huarong; Li, Guibai
Abstract : Ammonia removal was highly impacted by temperature and alkalinity. Fouling cake could remove a certain amount of ammonia. Abstract : A submerged, powdered activated carbon-membrane bioreactor (PAC-MBR) at a pilot-scale (2.2 m 3 h −1 ) was used to treat surface water with a high concentration of ammonia (~2.64 mg L −1 ) and a low alkalinity. The ammonia removal efficiency and its influencing factors ( i.e., temperature, alkalinity and aeration mode) were systematically investigated. The results showed that the PAC-MBR could effectively remove a high concentration of ammonia when the temperature was higher than 20 °C, and exhibited good resistance to ammonia fluctuation (fluctuation range: 1–3 mg L −1 ). The ammonia removal capacity of the PAC-MBR exponentially decreased as the temperature decreased over a temperature range from 13 °C to 24 °C. Alkalinity became the limiting factor when the temperature exceeded 24 °C, and ammonia removal linearly increased as the alkalinity increased. Moreover, intermittent aeration at an appropriate aeration interval was proven to provide enough oxygen for biological nitrification. Furthermore, the foulants attached on the membrane surface could also contribute to the ammonia removal during the filtration. The PAC-MBR process could serve as a potential option to address elevated levels of ammonia under steady and transient state operation.